Critical Discourse Analysis of News Reports on Junior High School Students Who Cannot Read in the Online Media Kompas.Com - Rilis Rosalenni; Teguh Setiawan (International Journal of Education, Vocational and Social Science, 2025)
The issue of education is an interesting topic that is often discussed from various sides by online media. This study aims to analyze the text structure, social cognition, and social context in the online media Kompas.com related to news about junior high school students who cannot read. This study uses a qualitative approach with data collection techniques through documentation, observation, and direct notes in the media. The data sources in this study came from three news items published in August 2024 by the online media Kompas.com regarding the phenomenon of junior high school students who can’t read. Data analysis techniques including of data condensation, data presentation, conclusions and verification. The results of the study show that the three news items published in the Kompas.com media have fulfilled the critical discourse analysis framework of Teun A. Van Dijk's model, namely; (1) macro structure; (2) superstructure; and (3) micro structure. Based on the critical discourse analysis that has been carried out, it can be concluded that the three news items have different discussions, but in principle they are interrelated. The components of the news text in the online media fulfill the Van Dijk discourse analysis model which consists of text structure, social cognition, and social analysis. This research can provide knowledge about the current reality of education in Indonesia and contribute to the development of critical discourse analysis theory in online media.